A case of post-traumatic minimally conscious state reversed by midazolam: Clinical aspects and neurophysiological correlates - Carboncini, Maria Chiara; Piarulli, Andrea; Virgillito, Alessandra; Arrighi, Pieranna; Andre, Paolo; Tomaiuolo, Francesco; Frisoli, Antonio; Bergamasco, Massimo; Rossi, Bruno; Bonfiglio, Luca (Restorative neurology and neuroscience, 2014)
Purpose: We describe the case of a subject in a post-traumatic Minimally Conscious State (MCS) who retrieved full interaction with the environment after midazolam infusion. We studied EEG correlates of the “awakening reaction” in the different domains of frequency, time and cortical topography, along with the intrinsic connectivity within both the task-positive and the linguistic network. Methods: EEG recorded before and after midazolam administration has been submitted to spectral power analysis, sLORETA analysis and intrinsic connectivity analysis within both functional networks. Results: A critical change in the power spectrum profile was observed after midazolam: a) the power between 1 and 12 Hz decreased, reaching its maximum difference with respect to pre-infusion at about 7 Hz and b) the power between 12 and 30 Hz increased, with a maximum difference at about 15 Hz. At the same time, midazolam induced significant connectivity changes, especially for these two frequency bands, within both functional networks. Conclusions: We advance some hypotheses about certain aspects of the recovery from the MCS both in terms of anatomo-functional correlations and functional brain systems and we make inferences about the role that some kind of ‘catatonic’ symptoms might play in determining and/or maintaining this peculiar clinical state.